Vascular Abnormalities in Peripapillary and Macular Regions of Behcet's Uveitis Patients Evaluated by Optical Coherence Tomography Angiography - Yan, Chun; Li, Fan; Hou, Min; Ye, Xiaoyuan; Su, Lishi; Hu, Yixin; Luo, Jiawen; Chi, Wei (Frontiers in Medicine, 2021)
Purpose: To investigate the involvement of peripapillary zone vascular abnormalities in Behcet’s uveitis (BU) and associated visual dysfunction. We evaluated the retinal and choroidal microvascular features in both macular and peripapillary areas of BU patients to identify vascular abnormalities contributing to reduced best-corrected visual acuity (BCVA) using optical coherence tomography angiography (OCTA). Methods: A prospective, observational study was conducted in 24 eyes of 13 patients with BU and 24 eyes of 15 healthy participants served as controls, received a standard eye examination and recorded by OCTA measurements of macular and peripapillary areas. Superficial capillary plexus (SCP) and deep capillary plexus (DCP) vascular densities, choroidal flow area, radial peripapillary capillary network (RPCN) density, foveal avascular zone (FAZ) area and perimeter, full retinal thickness (FRT), and peripapillary retinal nerve fiber layer thickness (pRNFLT) were measured, and correlations among microvascular, structural, and functional changes were assessed. Results: Our findings uncovered that the vascular density was significantly reduced in the peripapillary zone of BU eyes compared to healthy eyes, especially in the inferior subfields of the RPCN. The vascular densities of SCP and DCP quadrants within the macular zone had no significant difference between BU and control groups except for DCP density of the nasal parafoveal quadrant. Both FAZ area and perimeter were greater but without statistical significance in the BU group. Compared to healthy eyes, the choriocapillaris flow area was smaller while the FRT and pRNFLT were greater in the BU group. Notably, there was a significant correlation between the reduction in RPCN vascular density and decreased BCVA in BU patients. Conclusion: Based on OCTA, vascular changes associated with BU are more prominent in the peripapillary zone than in the macular zone. The vascular density of the RPCN could serve as a sensitive indicator to monitor BU pathogenic progression and treatment response using a non-invasively method of OCTA.